Aporte al conocimiento de la biología alimentaria de la Pollona Negra (Gallinula chloropus) en el Paraná Medio, Argentina - Laimanovich, Rafael C. (1993)
The feeding ecology of Galllinula chloropus galeata was studied collecting seasonal samples (spring, summer and winter). Twenty eight stomachs were analized. In each one the volume of each taxonomic entity was registered. The Weighted Resultant Index (Mohan and Sankaran 1988) and Seasonal amplitude of the niche (Levins 1968) were calculated. This study revealed for Galllinula chloropus galeata an oportunistic behavior. The trophic breath of the niche did not show seasonal variations.